PEEP or No PEEP: That Is Not the Question - Jesús Villar; Arthur S Slutsky (Canadian Respiratory Journal)
Generally, positive end-expiratory pressure (PEEP) is applied to improve oxygenation, and has been shown to improve gas exchange and lung compliance in acute lung injury, but it is not without risk. To date, no controlled outcome studies have been published to demonstrate the best method of choosing the level of PEEP. Furthermore, it is not known whether the application of PEEP contributes to lung damage or helps to ameliorate it. The authors review the goals of PEEP and the current evidence on its effects on lung injury and its clinical utility. In the absence of controlled clinical trials, the use of PEEP in acute respiratory distress syndrome needs to be guided by physiological principles that balance the beneficial effects of an increase in functional residual capacity, prevention of alveolar closure, redistribution of lung water and improved ventilation of low ventilation-perfusion areas against the potential harm of alveolar rupture (barotrauma and "volutrauma") and reduction in cardiac output.